2008
DOI: 10.1002/art.23791
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of caveolin 1 in patients with systemic sclerosis: Crucial role in the pathogenesis of tissue fibrosis

Abstract: Objective. Recent studies have implicated caveolin 1 in the regulation of transforming growth factor ␤ (TGF␤) downstream signaling. Given the crucial role of TGF␤ in the pathogenesis of systemic sclerosis (SSc), we sought to determine whether caveolin 1 is also involved in the pathogenesis of tissue fibrosis in SSc. We analyzed the expression of CAV1 in affected SSc tissues, studied the effects of lack of expression of CAV1 in vitro and in vivo, and analyzed the effects of restoration of caveolin 1 function on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
166
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(183 citation statements)
references
References 50 publications
8
166
6
Order By: Relevance
“…10 Interestingly, while bleomycin induces Cav-1 and Thus, Cav-2 modulates the fibrotic response by a mechanism that involves signal transduction pathways implicated in the control of apoptosis and proliferation, rather than the induction of molecules of the extracellular matrix, such as collagen. Since Cav-1 −/− mice also lack Cav-2 expression and are less severely affected by bleomycin treatment as compared with Cav-2 −/− mice (which still express Cav-1), we suggest that the balance of Cav-1 and Cav-2 determines the outcome of bleomycin-induced injury.…”
Section: Resultsmentioning
confidence: 99%
“…10 Interestingly, while bleomycin induces Cav-1 and Thus, Cav-2 modulates the fibrotic response by a mechanism that involves signal transduction pathways implicated in the control of apoptosis and proliferation, rather than the induction of molecules of the extracellular matrix, such as collagen. Since Cav-1 −/− mice also lack Cav-2 expression and are less severely affected by bleomycin treatment as compared with Cav-2 −/− mice (which still express Cav-1), we suggest that the balance of Cav-1 and Cav-2 determines the outcome of bleomycin-induced injury.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have supported this role of caveolin-1 in the development of tissue fibrosis [65][66][67][68]. For example, it was shown that caveolin-1 knockdown in vitro markedly increased collagen gene expression in normal human lung fibroblasts and that caveolin-1 was reduced in affected SSc lungs and skin [66] and in lung tissues and fibroblasts from patients with idiopathic pulmonary fibrosis [67,68]. Increasing caveolin-1 expression markedly improved bleomycin-induced pulmonary fibrosis [67].…”
Section: Protein Kinase C-δ (Pkc-δ) Pkc-δ Ismentioning
confidence: 94%
“…The localization of the TβRs in the EEA-1 positive compartment was responsible for downstream Smad activation, whereas their localization in caveolae lipid rafts caused recruitment of Smurf/Smad7 with subsequent receptor ubiquitination and rapid receptor degradation and turnover [63,64]. Numerous studies have supported this role of caveolin-1 in the development of tissue fibrosis [65][66][67][68]. For example, it was shown that caveolin-1 knockdown in vitro markedly increased collagen gene expression in normal human lung fibroblasts and that caveolin-1 was reduced in affected SSc lungs and skin [66] and in lung tissues and fibroblasts from patients with idiopathic pulmonary fibrosis [67,68].…”
Section: Protein Kinase C-δ (Pkc-δ) Pkc-δ Ismentioning
confidence: 99%
“…Each biopsy specimen is represented as the mean of four integrated density of fluorescence values per specimen. 31 Egr-2 expression was also examined in lungs from patients with SSc-associated pulmonary fibrosis undergoing lung transplantation and in normal donor lungs. The biopsy protocols were approved by the Institutional Review Board for Human Studies at the University of Pittsburgh, Pittsburgh.…”
Section: Immunodetection Of Egr-2 In Skin and Lung Biopsy Specimensmentioning
confidence: 99%